Proximity labeling proteomics reveals critical regulators for inner nuclear membrane protein degradation in plants - Aobo Huang (Nature Portfolio, 2020)
Maintaining protein integrity at the inner nuclear membrane (INM) is critical for eukaryotic cellular function. Here, using proximity-labeling proteomics, Huang et al. profile the INM in Arabidopsis and identify the CDC48 complex and PUX proteins as components of an INM protein degradation pathway.